Penggunaan Media dan Penerapan Teori Pembelajaran dalam Pendidikan Agama Islam - Dinda Salsabilla; Nur Azizah; Gusmaneli Gusmaneli (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to review more deeply various literatures related to the effectiveness of the use of media and the application of learning theories in Islamic Religious Education, both in terms of increasing understanding of religious concepts and in the formation of student character. The research method used in this study is literature review, which aims to analyze various literatures and previous studies related to the use of media and the application of learning theory in Islamic Religious Education. The results of this study show that learning media in Islamic Religious Education (PAI) plays an important role as an intermediary to make it easier for students to understand the material in a more interesting and interactive way. Various media, from whiteboards to digital applications, help overcome limitations in learning and reduce verbalism. In Islam, the Prophet Muhammad gave a direct example as a learning medium, which is an important basis for the application of media in PAI. Learning theories also support the effectiveness of PAI learning. Theories such as behavioristic, cognitive, constructivistic, and humanistic are applied to form habits of worship, encourage understanding of concepts, and promote student experience and interaction. The combination of the right media with learning theory can increase students' motivation and understanding in PAI.